Estimate depolarization level of reflected from hydrometeors radiowaves with amplitude method - Авер’янова, Ю.А.; Аверьянов, A.А.; Яновський, Ф.Й. (Proceedings of National Aviation University (archive), 2010)
In this paper the approach to estimate reflected from hydrometeors signal depolarization due to turbulence with a single unipolarized antenna is considered. The reflected radio wave depolarization is considered as informative parameter. It is shown that change of depolarization angle leads to the current amplitude fluctuations in the receiving antenna. It appears because the maximum value of receiving antenna current corresponds to the reception of the reflected from weather target wave with polarization that coincides with sounding wave polarization. In case of depolarization of reflected from weather target wave the receiving antenna current is defined as the projection on its beamwidth main axis.Taking into account the physics of atmospheric phenomena, the frequency characteristics of amplitude fluctuations due to dynamic processes differentiate from frequency characteristics of fluctuations that appear as a result of other processes influencing the signal amplitude. The estimate is made by the behavior of low-frequency envelope of radiosignal reflected from the hydrometeors assemble under the influence of atmospheric dynamic processes. The association analysis of turbulence intensity and low-frequency envelope change is made. The turbulence intensity estimate is made in the antenna of main polarization consequently at higher SNR level. This is important in case of small depolarization angles like in the most atmospheric phenomena.